Guidelines for the design of agricultural investment projects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Guidelines for the design of agricultural investment projects 1995 ISBN 92 5 103622 5